Association of midtrimester short femur and short humerus with fetal growth restriction. (28th November 2012) - de, Ana Alice Vidal; Carvalho, José Antônio; Figueiredo, Israel; Velarde, Luis Guillermo Coca; Marchiori, Edson
ABSTRACT Objective To investigate the association between the midtrimester presence of short femur and short humerus and intrauterine growth restriction. Methods This retrospective study included ultrasound examinations of 1043 fetuses. Fetuses with normal‐length bones were compared with fetuses that had femoral or humeral lengths below the 5th percentile for gestational age by Student's t‐test and the chi‐squared test. The association between short bones and fetal growth restriction development was evaluated by Fisher's exact test. Fetuses with estimated weight below the 10th percentile for gestational age and abnormal umbilical artery flow were considered to have growth restriction. Results Femoral and humeral lengths were normal in 974 (93.4%) fetuses; 19 (1.8%) fetuses had short femora, 65 (6.2%) had short humeri, and 15 (1.4%) had short femora and humeri combined. Of fetuses included in the analysis, 603 (57.8%) underwent Doppler examination. Short femur [odds ratio = 9.7, 95% confidence interval = 1.9–50.2, P = 0.03] and short humerus (odds ratio = 13, 95% confidence interval = 4.9–34.6, P < 0.001) were associated with fetal growth restriction. Conclusion Fetuses with midtrimester short femur, short humerus, or short femur and humerus combined require more intensive surveillance for growth restriction development. © 2012 John Wiley & Sons, Ltd.